VARIASI LATIHAN BERBASIS PERMAINAN DALAM MENGEMBANGKAN KEMAMPUAN SHOOTING FUTSAL - Fitriadi, Andika; Gustian, Uray; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractMany fond the athlete that his ability is still weak in doing the shooting have an impact on the shooting tha is done is often not accurate. In addition,there are weaknesses in the excerises athletes do namely the use of the target is settled while in the play futsal sometimes athletes need to be able to position yourself and do the shooting so as not to impeded the opponent and can produce goals. To that end,the study aims to find variastions of exercises can develop the ability to shooting athletes. The method used in this research isan exsperiment with the shape of the pre-exsperimental design. The results of the analysis using the game Performance Asesment Instrumen test (GPAI) shows there has been an increases shooting capabilities of the athlete. This is due to the variation of excerises that prepared able to stimulate the ability of the athlete to the variations of excercises that preparet able to stimulate the ability of the athlete to perform shooting according to the need at the time of the game. Conclusion the obtained variation of the exsercise-based game is able to develop the abilty of shooting athletes of futsal.Keywords: Variation Of Exercises, The Ability Of Shooting.